Mapping and identification of essential gene functions on the X chromosome of Drosophila. - Peter, A.; Schottler, P.; Werner, M.; Beinert, N.; Dowe, G.; Burkert, P.; Mourkioti, F.; Dentzer, L.; He, Y.; Deak, P.; Benos, P.V.; Gatt, M.K.; et al. (EMBO Reports, 2002)
The Drosophila melanogaster genome consists of four chromosomes that contain 165 Mb of DNA, 120 Mb of which are euchromatic. The two Drosophila Genome Projects, in collaboration with Celera Genomics Systems, have sequenced the genome, complementing the previously established physical and genetic maps. In addition, the Berkeley Drosophila Genome Project has undertaken large-scale functional analysis based on mutagenesis by transposable P element insertions into autosomes. Here, we present a large-scale P element insertion screen for vital gene functions and a BAC tiling map for the X chromosome. A collection of 501 X-chromosomal P element insertion lines was used to map essential genes cytogenetically and to establish short sequence tags (STSs) linking the insertion sites to the genome. The distribution of the P element integration sites, the identified genes and transcription units as well as the expression patterns of the P-element-tagged enhancers is described and discussed.